Knowledge payment research: status quo and key issues. Issue 2 (30th August 2019) - Qi, Tuotuo; Wang, Tianmei
Abstract : Purpose: Knowledge sharing has entered the stage of knowledge payment with the typical models of paid Q&A, live session, paid subscription, course column and community service. Numerous knowledge suppliers have begun to pour into the knowledge payment market, and users' willingness to pay for premium content has increased. However, the academic research on knowledge payment has just begun. Design/methodology/approach: In this paper, the authors searched several bibliographic databases using keywords such as "knowledge payment", "paid Q&A", "pay for answer", "social Q&A", "paywall" and "online health consultation" and selected papers from aspects of research scenes, research topics, etc. Finally, a total of 116 articles were identified for combing studies. Findings: This study found that in the early research, scholars paid attention to the definition of knowledge payment concept and the discrimination of typical models. With the continuous enrichment of research literature, the research direction has gradually been refined into three main branches from the perspective of research objects, i.e. knowledge provider, knowledge demander and knowledge payment platform. Originality/value: This paper focuses on discussing and sorting out the key research issues from these three research genres. Finally, the authors found out conflicting and contradictory research results and research gaps in the existing research and then put forward the urgent research topics.